The Effects of Frequent Therapeutic Administration of Artesunate-amodiaquine and Artemether-lumefantrine on Haematological Markers in BALB/c Mice - David Audu; Olufunmilayo Ajoke Idowu; Vinood B Patel; Musa Fakilahyel Mshelbwala; Adewumi Babatunde Idowu (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Artemisinin Combination Therapy (ACT) is readily available in malaria-endemic nations, leading to repeated drug usage by undiagnosed persons. Repeated use of ACT therapy by non-infected individuals may affect blood cells. This study explored how repeated artesunate-amodiaquine (A/A) and artemether-lumefantrine (A/L) treatment in non-infected mice affected haematological markers. 100 male BALB/c mice were randomly divided into 5 groups: non-infected and Plasmodium berghei NK65 infected treated with A/L and A/A 1X, 2X, 3X, 4X, 5X, and 6X, and the control group. Packed cell volume (PCV), Haemoglobin (Hb), and red blood cell (RBC) were reduced (p>0.05) non-significantly in the non-infected group treated with A/L or A/A six times compared to the control and infected groups. WBC rose in infected and non-infected mice treated with A/L or A/A 1X, 2X, 3X, and 6X, with a substantial rise in non-infected mice treated with A/L (p < 0.01) and A/A (p < 0.001) three times. WBC mainly rose due to lymphocytes, although neutrophils decreased. Repeated therapeutic use of A/L and A/A without infection may cause a haematological change. Continuous efforts are needed to educate the public about screening for malaria parasites before using drugs.